Validation of the slaughterhouse porcine heart model for ex-situ heart perfusion studies - Selma E Kaffka genaamd Dengler; Mudit Mishra; Sjoerd van Tuijl; Saskia CA de Jager; Joost PG Sluijter; Pieter A Doevendans; Niels P van der Kaaij (SAGE Journals, 2023)
Introduction
To validate slaughterhouse hearts for ex-situ heart perfusion studies, we compared cold oxygenated machine perfusion in less expensive porcine slaughterhouse hearts (N = 7) to porcine hearts that are harvested following the golden standard in laboratory animals (N = 6).
Methods
All hearts received modified St Thomas 2 crystalloid cardioplegia prior to 4 hours of cold oxygenated machine perfusion. Hearts were perfused with homemade modified Steen heart solution with a perfusion pressure of 20–25 mmHg to achieve a coronary flow between 100–200 mL/min. Reperfusion and testing was performed for 4 hours on a normothermic, oxygenated diluted whole blood loaded heart model. Survival was defined by a cardiac output above 3 L with a mean aortic pressure above 60 mmHg.
Results
Both groups showed 100% functional survival, with laboratory hearts displaying superior cardiac function. Both groups showed similar decline in function over time.
Conclusion
We conclude that the slaughterhouse heart can be used as an alternative to laboratory hearts and provides a cost-effective method for future ex-situ heart perfusion studies.
Keywords: Cardiology; 110323 Surgery